2015
DOI: 10.1245/s10434-015-4623-z
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy Followed by Interval Debulking Surgery and the Risk of Platinum Resistance in Epithelial Ovarian Cancer

Abstract: IDS correlates with a higher risk of the development of platinum resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 24 publications
4
31
0
Order By: Relevance
“…However, if rates of complete surgical cytoreduction were more than double in IDS arm compared with PDS arm (51.2% vs 19.4% in the study of Vergote et al 21 and 39% vs 17% in that of Kehoe et al, 22 the prognostic relevance of the achievement of no gross RD after surgery could be quite different for patients undergoing PDS and for those undergoing IDS. In the present investigation, 30 In the present investigation, among the patients with no gross RD after surgery, tumor recurred in 57.4% of the 115 who underwent PDS vs 87.5% of the 32 who underwent IDS (P = 0.001). The IDS group showed a trend to a higher recurrence rate within 6 months (6.2% vs 1.7%) and a significantly higher recurrence rate between 6 and 12 months (37.5% vs 15.6%; P = 0.01) compared with PDS group.…”
Section: Discussionsupporting
confidence: 45%
“…However, if rates of complete surgical cytoreduction were more than double in IDS arm compared with PDS arm (51.2% vs 19.4% in the study of Vergote et al 21 and 39% vs 17% in that of Kehoe et al, 22 the prognostic relevance of the achievement of no gross RD after surgery could be quite different for patients undergoing PDS and for those undergoing IDS. In the present investigation, 30 In the present investigation, among the patients with no gross RD after surgery, tumor recurred in 57.4% of the 115 who underwent PDS vs 87.5% of the 32 who underwent IDS (P = 0.001). The IDS group showed a trend to a higher recurrence rate within 6 months (6.2% vs 1.7%) and a significantly higher recurrence rate between 6 and 12 months (37.5% vs 15.6%; P = 0.01) compared with PDS group.…”
Section: Discussionsupporting
confidence: 45%
“…Three retrospective trials [ 12 – 15 ] also demonstrated that patients in the NACT-IDS group had a higher risk of platinum-resistant recurrence than those who underwent PDS. However, in studies by Rauh-Hain [ 12 ] and da Costa, [ 13 ] no significant difference in platinum-resistant disease at the first relapse was observed, whereas the risk of platinum-resistant disease at the second relapse was higher in both Rauh-Hain's (adjusted OR 4.06, P = 0.001) and da Costa's (adjusted HR 1.92, P = 0.009) studies. Moreover, in Petrillo's and Rauh-Hain's studies, [ 14 ] there was a significant difference in platinum-resistant disease at first recurrence only in the univariate analysis.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, different retrospective series suggested a strong association between tumor volume, suboptimal cytoreduction and NACT + IDS with platinum resistance. 24 , 25 , 26 The most widely accepted hypothesis implicates the outgrowth of resistant clones, which are usually present at low rates before initial treatment and are greater in large tumor volumes treated with platinum compounds. 27 …”
Section: Discussionmentioning
confidence: 99%